Гендер та релігія - Кирпа, Ю. О. (ХНУРЕ, 2022)
This work is devoted to the study of what images of women and men Christianity and Islam form, dand what models of behavior are normalized for them. To achieve this goal, a number of tasks was solved, in particular, fragments of the religious texts of the Bible and the Koran were analyzed, scientific sources devoted to the problem of the influence of religion on gender relations were analyzed.
Keywords: гендер; релігія